Community service sector resilience and responsiveness during the COVID‐19 pandemic: The Australian experience. Issue 4 (31st May 2021) - Coram, Veronica; Louth, Jonathon; Tually, Selina; Goodwin‐Smith, Ian
Abstract: The COVID‐19 pandemic is a public health, economic and social crisis that is likely to have lasting consequences, including increased rates of financial hardship, housing insecurity, mental health problems, substance abuse and domestic violence. Workers in the community service sector have continued to support some of the most vulnerable and disadvantaged Australians during the pandemic, while also delivering services to new groups experiencing the economic impacts of virus suppression strategies. We surveyed community service sector workers from across Australia in three snapshots during April–May 2020 and found that perceptions of acute needs and organisational pressure points shifted even through this short period. While the sector faced significant challenges, it responded to the initial phase of the pandemic with flexibility, a strongly client‐centred approach and a re‐emphasis on collaboration between services. The community service sector's demonstrated capacity for agility and rapid adaptation suggests it is well placed to provide critical supports to those affected by crisis situations and everyday disadvantage. However, the sector's capacity to perform this role effectively depends on strong, stable government supports for all Australians in need.